2021
DOI: 10.3389/fphys.2021.739185
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Site Does Not Affect Changes in Pulse Wave Velocity but Treatment Length and Device Selection Are Associated With Increased Pulse Wave Velocity After Thoracic Endovascular Aortic Repair

Abstract: Background: Endovascular treatment of aortic aneurysm is associated with an increase in pulse wave velocity (PWV) after surgery. However, the effect of different types of endovascular devices on PWV at different sites of the thoracic aorta remains unclear.Objectives: The purposes of this study were (1) to investigate the changes in PWV after endovascular treatment of thoracic aortic aneurysm; (2) to evaluate whether there is a difference in the changes in PWV at different treatment sites; and (3) to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“… 32 In addition, it was demonstrated more recently that treatment length was an independent factor related to PWV increase. 35 The same study also showed that treatment site as a sole factor did not have a different effect on PWV.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“… 32 In addition, it was demonstrated more recently that treatment length was an independent factor related to PWV increase. 35 The same study also showed that treatment site as a sole factor did not have a different effect on PWV.…”
Section: Resultsmentioning
confidence: 84%
“…The review identified 10 studies (Table 3) reporting the influence of thoracic endografts, following TEVAR, on arterial stiffness. [27][28][29][30][31][32][33][34][35][36] Most studies on TEVAR utilized PWV to measure arterial stiffness. 27,28,30,33,35 In 2017, PWV was used for measuring the arterial stiffness in patients following TEVAR for descending thoracic aorta disease, showing remarkable increase 6 months postoperatively.…”
Section: Studies Assessing Arterial Stiffness In Patients With Taa Be...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in their study, Hori et al revealed the idea that the selection of a specific device is related to increased PWV after TEVAR. Furthermore, Hori et al found that the treatment length of the thoracic aorta and the length of the endograft are independent factors that are positively correlated with an increase in PWV after TEVAR, although the treatment site does not have an independent effect on the PWV [29]. On the contrary, in their study, Yamashita et al found that the treatment length and device type were not predictors of an increase in the PWV after TEVAR [30].…”
Section: Aortic Stiffness After Evarmentioning
confidence: 92%
“…VP-1000 Plus vascular screening device 2 [356,323] VaSera VS-1500 vascular screening system 1 [353] BOSO-ABI System 100 device 1 [359] BP-203RPEIII networked arterial stiffness detection device 1 [331] Mylab90 device 1 [125] Estimated PWV using age and mean blood pressure 1 [326] Omron Colin device 1 [325] Volume plethysmography device 1 [322] SOMNOscreen plus device 1 [349] DOI: 10.1159/000527765…”
Section: Analytic Considerationsmentioning
confidence: 99%